Analisis Kenyamanan Thermal pada Gedung Gelanggang Mahasiswa Prof. A. Madjid Ibrahim Universitas Syiah Kuala - Teuku Zulfadli; Ahmad Syuhada; Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2013)
Student center building Prof. A. Madjid Ibrahim who has been reconstructed back in use as a meeting hall with a capacity of 500 people, but the results showed that the temperature in the room is empty conditions at 13:00 pm 32.7 0C, humidity 61%. The time charged 30 people occupants temperature during hours the same 33.5 0C, humidity 60%. While over 100 people filled the temperature at the same time at 34.4 0C, 57% humidity, and wind speed to the three conditions is 0 m / s. From the results of research on different floors 1 and 2 indoor temperature difference measured at 09.00 pm with the comfort standard is 2.2 0C obtained under thermal comfort in the building arena student Prof. A. Madjid Ibrahim is not achieved because the temperature of indoor air temperature outside the comfort standard SNI T03-6572.